2015
DOI: 10.1515/jms-2016-0195
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between academic self-efficacy, intrinsic motivation, and perceived competence

Abstract: This study investigated the moderating role of intrinsic motivation for military studies on the relationship between academic self-efficacy and change in perceived military competence. We present two concurrent hypotheses based on theoretical interaction effects of intrinsic motivation. Data from 245 cadets from three military academies revealed a positive relationship between self-efficacy and an increase in perceived military competence only for cadets with lower levels of intrinsic motivation. This suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 62 publications
3
22
0
1
Order By: Relevance
“…Self-efficacy. In order to measure self-efficacy in a military context a 7-item scale was used (Buch, Säfvenbom, & Boe, 2015). Sample items include "will manage to complete the military training" and "will achieve a result I can be proud of".…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy. In order to measure self-efficacy in a military context a 7-item scale was used (Buch, Säfvenbom, & Boe, 2015). Sample items include "will manage to complete the military training" and "will achieve a result I can be proud of".…”
Section: Methodsmentioning
confidence: 99%
“…Academic self-efficacy. As we wanted to measure self-efficacy at T1 and T2, we developed a seven-item scale that was specifically designed to capture the selfefficacy beliefs that participants would have regarding their ability to be successful in completing their military training and education (Buch, Säfvenbom, & Boe, 2015). The Self-Efficacy Scale was developed because individuals have different self-efficacy beliefs in different activities and across domains, and as a consequence of this "there is no single all-purpose measure of self-efficacy with a single validity coefficient" (Bandura, 2012, p. 15).…”
Section: Methodsmentioning
confidence: 99%
“…Based upon these studies, it is therefore fair to say that psychological skills are important for both soldiers and officers. Contradicting this, Buch, Säfvenbom, and Boe (2015) found that for military cadets with a high level of intrinsic motivation, self-efficacy was of less importance as a mediator to increase their perception of their military competence. A preliminary conclusion one might draw from the above mentioned studies is that the role of self-efficacy in a military environment is still somewhat ambiguous and not well-defined clear-cut.…”
Section: Self-efficacymentioning
confidence: 99%
“…In this study, both problem-solving selfefficacy and academic self-efficacy were positively correlated with student motivation. University studies have confirmed a strong correlation between students' self-efficacy skills and academic motivation, which deter procrastination habits (Cerino, 2014) and maintain the motivation to learn course material (Ibrahim & Jaaffar, 2017). Since efficacious students believe in their abilities to perform well during the problem-solving process in university courses, students are likely to be motivated to put forth more effort than low self-efficacy students in course assessments (Lindblom-Ylänne, Haarala-Muhonen, Postareff, & Hailikari, 2017).…”
Section: Self-efficacy and Motivationmentioning
confidence: 95%